1998
DOI: 10.1089/jwh.1998.7.1157
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Supplementation Alleviates Premenstrual Symptoms of Fluid Retention

Abstract: We investigated the effect of a daily supplement of 200 mg of magnesium (as MgO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 13 publications
0
47
0
2
Order By: Relevance
“…160 A recent study reported that 80 mg daily of pyridoxine was superior to placebo in relieving anxiety and mood premenstrual symptoms but not physical symptoms. 161 Two small RCTs have suggested the efficacy of magnesium, 162,163 but other studies have failed to document magnesium deficiency in women with PMDD or improvement of premenstrual symptoms with supplemental magnesium when compared with placebo. 164 An RCT reported superior efficacy for trytophan, compared with placebo, in women with PMDD, 165 and an early study that suggested efficacy for vitamin E deserves replication.…”
Section: Dietary Supplementationmentioning
confidence: 99%
“…160 A recent study reported that 80 mg daily of pyridoxine was superior to placebo in relieving anxiety and mood premenstrual symptoms but not physical symptoms. 161 Two small RCTs have suggested the efficacy of magnesium, 162,163 but other studies have failed to document magnesium deficiency in women with PMDD or improvement of premenstrual symptoms with supplemental magnesium when compared with placebo. 164 An RCT reported superior efficacy for trytophan, compared with placebo, in women with PMDD, 165 and an early study that suggested efficacy for vitamin E deserves replication.…”
Section: Dietary Supplementationmentioning
confidence: 99%
“…Deficiencies in plasma (Posaci et al 1994), red blood cell (RBC; Abraham et al 1981;Rosenstein et al 1994;Sherwood et al 1986;Stewart et al 1986), and mononuclear blood cell (MBC; Rosenstein et al 1994) Mg concentrations have been observed in women with PMS relative to women without PMS. Additionally, two placebo-controlled, double-blind, prospective clinical trials of oral Mg supplementation in women with PMS found that Mg was superior to placebo in the alleviation of mood (Facchinetti et al 1991) and fluid retention symptoms (Walker et al 1998). One interpretation of these findings is that women with PMS are Mg deficient and that Mg replacement may be a treatment for some of the core symptoms of this disorder.…”
mentioning
confidence: 99%
“…Nutritional supplements which have proven efficacy that have been evaluated in women with PMS include vitamins, calcium, magnesium, multivitamin/mineral supplements, evening primrose oil and chaste-tree berry (Wyatt and colleagues 1999;Kleijnen et al 1990;London et al 1987;Dickerson 2003;Thys-Jacobs et al 1998;Facchinetti et al 1991;Walker et al 1998). …”
Section: Non-pharmacologic Treatments Of Pmsmentioning
confidence: 99%
“…However, the possibility that renal calculi might develop has been a concern with calcium supplementation (Frye & Silverman 2000). Magnesium supplementation was also found to be effective in alleviating some of the PMS symptoms in Italy (Facchinetti et al 1991) and in the United Kingdom (Walker et al 1998 should not be routinely recommended for women with PMS since high dose of this vitamin for prolonged periods of time can cause neurological symptoms.…”
Section: Non-pharmacologic Treatments Of Pmsmentioning
confidence: 99%